Assessing dyslexia in higher education: The York adult assessment battery-revised - Warmington, M; Stothard, SE; Snowling, M (2013)
Although there are a number of standardised measures to assess dyslexia in children, there are comparatively fewer instruments suitable for the assessment of dyslexia in adults. Given the growing number of students entering UK higher education institutions, there is a need to develop reliable tools for assessing the additional needs of those with dyslexia and related difficulties. This study reports data from a revised version of the York Adult Assessment: An Assessment Battery for Dyslexia Screening in Higher Education. The current York Adult Assessment-Revised (YAA-R) is an assessment battery consisting of tests of reading, spelling, writing and phonological skills. Data from a normative sample of 106 adults without dyslexia and a validation sample of 20 adults with dyslexia illustrate significant group differences on the tests comprising the YAA-R. Additionally, the YAA-R has good discriminatory power yielding 80% sensitivity and 97% specificity. Taken together, the YAA-R is a suitable test battery for the assessment and identification of dyslexia in university students. © 2012 The Authors. Journal of Research in Special Educational Needs © 2012 NASEN.